Natural gas utilization in China: Development trends and prospects. (November 2018) - Wang, Zhongyuan; Luo, Dongkun; Liu, Linlin
Abstract: It has been an important objective in China's energy development strategy to accelerate the promotion of natural gas utilization, cultivate main sources of natural gas, and increase the proportion of natural gas consumption. Based on the analysis of the development of natural gas utilization in China over the past 3 decades by means of classified and comparative research, this paper reveals the shift in the development pattern of China's natural gas utilization structure from the domination of industrial gas and chemical gas to a relative balance among industrial fuel, urban gas, and power generation gas. Sustained and steadily growing natural gas is an important basis for the rapid growth of natural gas utilization. Maintaining moderate growth in the natural gas transmission and distribution network is an important guarantee for the rapid growth of natural gas utilization. The slowdown in the world's economic growth has not caused any significant adverse impact on the rapid growth in China's electricity generation gas. The natural gas utilization policy has no effect on the adjustment of industrial fuel gas any longer. Industrial fuels and chemical gas are greatly subject to natural gas prices. Based on China's energy consumption targets for 2020 and 2030, this paper estimates the gas consumption of major gas areas and their development position, namely, more development space for industrial fuels, still rapid growth in urban gas but hardly major breakthroughs in gas proportion, rapid growth in power generation gas and a more prominent role in peak shaving, sustained high growth in transportation gas and challenges from new energy and low oil prices, and a significant decline but still a large scale in chemicalgas.